Effects of tillage methods on soil physical properties and maize growth in a saline–alkali soil. Issue 5 (24th August 2021) - Chen, Tianyu; Zhang, Yifei; Fu, Jian; Yang, Li; Chi, Yuxin; Yang, Kejun; Wang, Yufeng
Abstract: Soil sodicity and salinization is a major issues concerning agricultural production in northeast China. The effects of six treatments—no tillage (NT), no tillage and subsoiling (NTS), rotary and ridge tillage (RT), rotary and ridge tillage and subsoiling (RTS), rotary and flat tillage (FT), and rotary and flat tillage and subsoiling (FTS)—on soil physical and chemical properties and yields were compared from 2016 to 2018. The results showed that compared with the RT treatment, which is the traditional tillage method in this area, and the FT treatment, the NT treatment increased the soil water content (SWC) during the first‐leaf growth stage (V1). The use of subsoiling increased the average daily temperature and the soil thermal time (TTsoil ). Subsoiling contributed to the growth and development of deep roots and increased leaf area index (LAI) to intercept more radiation. The NTS treatment increased grain yield of maize ( Zea mays L.) by 2.7–15.2%, nitrogen use efficiency (NUE) by 4.2–14.4%, and water use efficiency (WUE) by 5.4–16.5% compared with RT. In conclusion, NTS soil management practices appear to be a sustainable approach to farming in the semiarid region of the Songnen Plain. Core Idea: Subsoiling reduced the BD and increased the SWC and average daily temperature. The NT treatment reduced soil salinity.